APPLICATION OF THE K-MEANS METHOD FOR PREPARATION OF NEW STUDENTS ENTRY SELECTION - Nur Fuad; Listiarini Edy Sudiati; Ninik Haryani (SOSCIED, 2022)
The moment of acceptance of new students is often an event for schools to get potential students, especially in the academic field. This is done because the good name of the school is strongly influenced by the achievements of its students either through competitions, art events or other activities. But on the other hand, many prospective new students do not understand what potential is in them. For that, we need a system that is able to classify students based on student potential. The grouping uses the National Examination scores as the basis for this grouping. The clustering method used is the K-Means Clustering method. The data is divided into two clusters which are divided into general school groups and madrasah school groups. From the results of clustering, it was found that 6 students were in the general school group and 11 students in the madrasa school group.